How to Facilitate Decision-Making for Hematopoietic Stem Cell Transplantation in Patients With Hemoglobinopathies. The Perspectives of Healthcare Professionals - Mekelenkamp, Hilda; Zanten, Herma van; Vries, Martine de; Lankester, Arjan; Smiers, Frans (Frontiers in Pediatrics, 2021)
Hematopoietic stem cell transplantation decision-making for hemoglobinopathy patients is a complex process, and it remains difficult for health care professionals to decide whether and when a hematopoietic stem cell transplantation should be offered. Gaining insight into health care professionals’ considerations is required to understand and optimize this decision-making process. A qualitative interview study using semi-structured interviews with eighteen health care professionals. Data were thematically analyzed. Two main themes emerged from the data: 1) Experiencing the influence of a frame of reference and 2) Feeling responsible for guided decision-making. The frame of reference, meaning the health care professionals’ knowledge and experiences regarding hematopoietic stem cell transplantation, influenced the guided decision-making process. Subsequently, three subthemes evolved from the second theme: a) weighing up disease severity against possible complications, b) making an effort to inform, and c) supporting the best fitting decision for the individual patient. The health care professionals' frame of reference determined the hematopoietic stem cell transplantation decision-making process. This demands reflection on the health care professionals’ own frame of reference and its influence on decision-making. Furthermore, reflection on the frame of reference is needed by exchange of knowledge and experiences between referring and referred-to healthcare professionals in an open and two-way direction. The transplantation teams have a responsibility of keeping the frame of reference of their referring colleagues up to date and referring health care professionals should share their feelings regarding hematopoietic stem cell transplantation. To guide patients, a shared decision-making approach is supportive, in which eliciting the patients’ preferences is highly important. Health care professionals can refine the decision-making process by guiding patients in eliciting their preferences and including these in the decision.